Like pigs, and unlike other breeds of cattle examined, mature Angus-derived adipocytes may extrude lipid prior to proliferation in vitro - Wei, Shengjuan (Landes Bioscience, 2012)
A large number of studies have shown that mature adipocytes are able to dedifferentiate in vitro into progeny cells, which possess proliferative capacity and mutilineage potential. Our present study confirms that mature adipocytes derived from Angus cattle also dedifferentiate into proliferative-competent progeny cells. However, this report is unlike any published for all other breeds of cattle we have worked with or that we have seen in published reports, in which mature adipocytes retain and distribute lipids into daughter cells symmetrically or asymmetrically. In the present work, we noted that Angus-derived mature adipocytes extruded a majority of their cellular lipid droplets prior to cell division. In this manner, these cells are processing lipid in a manner observed in mature adipocytes isolated from swine tissue. These results suggest that regulation of the mechanism(s) underlying lipid processing might be different between and within animal breeds. Lipid processing in beef-derived adipocytes during dedifferentiation may serve as a unique animal model for studying lipid metabolism during reverse adipogenesis.